Drosophila melanogaster Hsp22: a mitochondrial small heat shock protein influencing the aging process - Morrow, Geneviève; Tanguay, Robert M. (Frontiers in Genetics, 2015)
Mitochondria are involved in many key cellular processes and therefore need to rely on good protein quality control (PQC). Three types of mechanisms are in place to insure mitochondrial protein integrity: reactive oxygen species (ROS) scavenging by anti-oxidant enzymes, protein folding/degradation by molecular chaperones and proteases and clearance of defective mitochondria by mitophagy. Drosophila melanogaster Hsp22 is part of the molecular chaperone axis of the PQC and is characterized by its intra-mitochondrial localization and preferential expression during aging. As a stress biomarker, the level of its expression during aging has been shown to partially predict the remaining lifespan of flies. Since over-expression of this small heat shock protein (sHSP) increases lifespan and resistance to stress, Hsp22 most likely has a positive effect on mitochondrial integrity. Accordingly, Hsp22 has recently been implicated in the mitochondrial unfolding protein response (mtUPR) of flies. This review will summarize the key findings on D. melanogaster Hsp22 and emphasis on its links with the aging process.